A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from shallow coastal waters in Japan - Komai, Tomoyuki; Yoshida, Ryuta (Zootaxa, 2020)
A new species of diogenid hermit crab, Diogenes minimus, is described and illustrated on the basis of material from shallow subtidal waters (5–19 m) in central Japan. It appears close to D. holthuisi Asakura & Tachikawa, 2010, but easily distinguished from the latter by the shape of the antennal acicle, non-elongate male left cheliped and the armature of the right cheliped merus. Including the new species, 14 identified species of Diogenes are now known from Japanese waters. A brief overview on species of Diogenes recorded from Japanese waters is given.